Glycocalyx scaffolding with synthetic nanoscale glycomaterials. (15th June 2017) - Huang, Mia L.; Purcell, Sean C.; Verespy III, Stephen; Wang, Yinan; Godula, Kamil
Abstract : A cell surface engineering method allows for building glycan complexity with control over nanoscale presentation. Abstract : We report a method for programming complexity into the glycocalyx of live cells. Via a combination of glycomaterial synthesis and membrane remodeling, we have engineered cells to display native-like, mixed sialoglycan populations, while confining the activity of each glycan into a specific nanoscale presentation.